Recent Advances in Rice Research 2021
DOI: 10.5772/intechopen.93801
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Rice in Africa: Progress, Prospects, and Challenges

Abstract: Hybrid rice varieties exploit the phenomenon of heterosis to out-yield their inbred counterpart to increase productivity per unit area. Unlike inbred rice varieties whose seeds could be used for replanting season after season, farmers will have to purchase seeds of hybrids every season to obtain the expected yield and other quality attributes. While the hybrid system is a disadvantage to farmers in terms of mandatory seed purchase, it serves as a motivation and opportunity for private seed companies to recoup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The process of developing hybrid rice by conventional breeding approaches involves manually cross-pollinating two or more inbred rice lines that possess desirable qualities ( Figure 1 ), which results in the production of hybrid offspring with superior attributes [ 30 ]. These inbred lines are typically developed through several generations of self-pollination to create genetically stable lines that breed true [ 52 ].…”
Section: Breeding Techniques For Producing Hybrid Ricementioning
confidence: 99%
“…The process of developing hybrid rice by conventional breeding approaches involves manually cross-pollinating two or more inbred rice lines that possess desirable qualities ( Figure 1 ), which results in the production of hybrid offspring with superior attributes [ 30 ]. These inbred lines are typically developed through several generations of self-pollination to create genetically stable lines that breed true [ 52 ].…”
Section: Breeding Techniques For Producing Hybrid Ricementioning
confidence: 99%
“…Introduced in 1973 by Chinese Academician Yuan Longping, hybrid rice increases total rice yields by 44% [6]. A study in 2020 conducted in Africa when hybrid rice technology was first introduced suggested that over traditional inbred types cultivated in identical circumstances, a yield advantage of 15% to 30% has been documented [7]. Such an increase is enough to prevent starvation at least among the younger generation.…”
Section: In-depth Analysis Of Mortality Crisis and A More Comprehensi...mentioning
confidence: 99%